2010
DOI: 10.1248/cpb.58.1655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Docking Calculations on X-Ray Structures Using CONSENSUS-DOCK

Abstract: NoteDuring the past decade, in silico approaches for seeking active compounds to target proteins have become more popular in drug discovery due to significant advances in computer hardware and software. There are a large number of docking programs (e.g., DOCK, 1) AutoDock, 2) GOLD, 3) GLIDE, 4) Ph-DOCK 5) ), and many applications of these programs have been reported by various research groups. In major pharmaceutical companies, in silico approaches have been used to solve complicated drug design problems, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…If no information on the scoring function performance for a particular target is available, a worthwhile option can be to look at the scoring function performance on highly similar targets provided that any exist. In case no related targets exist, the use of consensus scoring schemes may be the protocol of choice due to their relatively high robustness to outliers [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Given the lucky situation that structural and/or affinity data for the target at hand is available, assessing the performance of these scoring functions within the same docking package is obviously the most effective way for making an informed decision about which one to choose in the discovery process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If no information on the scoring function performance for a particular target is available, a worthwhile option can be to look at the scoring function performance on highly similar targets provided that any exist. In case no related targets exist, the use of consensus scoring schemes may be the protocol of choice due to their relatively high robustness to outliers [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Given the lucky situation that structural and/or affinity data for the target at hand is available, assessing the performance of these scoring functions within the same docking package is obviously the most effective way for making an informed decision about which one to choose in the discovery process.…”
Section: Resultsmentioning
confidence: 99%
“…As shown by O'Boyle et al [22], the performance of a specific scoring function is almost always better if it is used to rescore poses generated using another scoring function than if the function is directly used to generate the poses. Many studies have shown that consensus docking schemes benefit from this observation [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In order to evaluate the pose prediction performance of the scoring functions more objectively, the conformational space should be sampled as accurately as possible.…”
Section: Introductionmentioning
confidence: 99%
“…This can be very useful, as it combines the advantages and simultaneously attenuates the shortcomings of each method [64]. Examples of consensus scoring functions are MultiScore, X-Cscore, GFscore, SCS, SeleX-CS and CONSENSUS-DOCK [65][66][67][68][69][70]. Table 2 provides a list of several scoring functions implemented in the most frequently used molecular docking programs.…”
Section: Evaluation Of Binding Energeticsmentioning
confidence: 99%
“…Pose prediction: RMSD [94] Glide XP, Glide SP, Surflex, FlexX, GOLD 4 targets: angiotensin-converting enzyme (ACE), cyclooxygenase 2 (COX-2), thrombin and human immunodeficiency virus 1 (HIV-1) protease; 50 actives and 950 decoys from the MDL Drug Data Report (MDDR) for each target [204] GOLD: GoldScore, ChemScore, ASP; AutoDock; Surflex-Dock; FRED: Shapegauss, PLP, CGO, Chemgauss 2, Chemgauss 3 4 sarco/endoplasmic reticulum calcium ATPase (SERCA) complexes for pose prediction; 22 SERCA inhibitors for affinity prediction Pose prediction: RMSD; affinity prediction: score vs. logIC 50 [205] PDBbind (610)…”
Section: Dud (11)mentioning
confidence: 99%
“…Other examples of consensus scoring include VS against kinases; [29] VoteDock development; [17] a combination of quantitative structure-binding affinity relationship (knowledge based) and MedusaScore (force field based); [91] a combination of MCSS and GOLD docking with MM/GBSA rescoring for fragments; [32] a combination of AutoDock4 and AutoDock Vina; [92] a combination of DOCK4, [93] FlexX, and PMF; [94] and HarmonyDOCK. [95] Machine-learning approaches to scoring function development One of the postulated weaknesses of scoring, resulting in poor affinity prediction, is the assignment of a common (i.e., system-independent) set of weights to the individual functional terms and the incorrect assumption that these weights are additive in their contribution to binding affinity.…”
Section: Consensus Scoringmentioning
confidence: 99%